PENGARUH PENGGUNAAN STRATEGI INKUIRI BERBANTUAN MEDIA AUDIOVISUAL TERHADAP KETERAMPILAN MENULIS TEKS EKSPLANASI SISWA KELAS VIII SMP NEGERI 1 PAINAN - Dewi, Ratih Kusuma; Thahar, Harris Effendi; Arief, Ermawati (Universitas Negeri Padang, 2018)
This research aims to (1) describe the level of empirical research text writing skills of students of class VIII SMP Negeri 1 Painan without using audiovisual media-assisted inkuiri strategy, (2) describe the level of writing skills text empirical research grade VIII SMP Negeri 1 Painan using audiovisual media-assisted inkuiri strategies, and (3) describe the influence of the use of audiovisual media-assisted inkuiri strategy against empirical research text writing skills grade VIII SMP Negeri 1 Painan. The theory used in the study of empirical research text writing skills, strategies, and audiovisual media inkuiri. Type of this research is quantitative research using experimental methods. The selected experimental methods i.e. artificial experiments or design with the design experiment quasy static two groups. The population in this research is grade VIII SMP Negeri 1 Painan listed in the lesson 2016/2017 of 238 students. A sample of these studies amounted to 32 students. Sampling this research was conducted with the purposive sampling technique. This research data is a score test results of empirical research text writing skills without the use of audiovisual media-assisted inkuiri strategies and score the test results of empirical research text writing skills using audiovisual media-assisted inkuiri strategy.Â Kata Kunci: inkuiri, audiovisual media strategy, text of empirical research